Power lines vegetation enchroachment monitoring based on satellite stereo images using stereo matching - Qayyum A.; Malik A.S.; Saad M.N.M.; Iqbal M.; Abdullah M.F.; Abdullah T.A.R.B.T.; Ramli A.Q. (Institute of Electrical and Electronics Engineers Inc., 2023)
Continuous monitoring the vegetation encroachment for high voltage transmission lines is challenging task for electrical distribution authorities. The enchroachment causes interruption which results in blackouts. It also endures great cost to the authorities for maintenance and damage compensation. There are many methods available to monitor growth of vegetation near transmission line poles. However, these methods are constrained with time consumption and cost. In this paper,a new method based estimating 3D height/depth of vegetation or trees near transmission lines using satellite stereo vision is proposed. We have evaluated local methods of stereo matching using Quickbird Satellite stereo images and compare the performance of stereo matching cost functions in terms of processing speed and time. Results show that our proposed algorithm is faster and more accurate than the existing algorithm for disparity calculation. 2014 IEEE.